OBSERVATION OF CONDUCTION ELECTRONS IN SB-IMPLANTED SNO2 BY ULTRAVIOLET PHOTOEMISSION SPECTROSCOPY - Rastomjee, C; Egdell, R; Lee, M; Tate, T (1991)
Conduction electrons introduced by 90 keV Sb ion implantation into SnO2 thin films have been observed in photoemission spectra excited with He(I) (hv = 21.2 eV) radiation. The carrier concentration is smaller than expected from the surface Sb concentration seen in XPS. This is discussed in terms of trapping of electrons in Sb(III)-like lone pair states associated with surface Sb ions. © 1991.